2011
DOI: 10.1371/journal.pone.0016439
|View full text |Cite
|
Sign up to set email alerts
|

MoVam7, a Conserved SNARE Involved in Vacuole Assembly, Is Required for Growth, Endocytosis, ROS Accumulation, and Pathogenesis of Magnaporthe oryzae

Abstract: Soluble NSF attachment protein receptor (SNARE) proteins play a central role in membrane fusion and vesicle transport of eukaryotic organisms including fungi. We previously identified MoSce22 as a homolog of Saccharomyces cerevisiae SNARE protein Sec22 to be involved in growth, stress resistance, and pathogenicity of Magnaporthe oryzae. Here, we provide evidences that MoVam7, an ortholog of S. cerevisiae SNARE protein Vam7, exerts conserved functions in vacuolar morphogenesis and functions in pathogenicity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
100
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 44 publications
1
100
0
Order By: Relevance
“…Cell wall composition in M. oryzae plays an important role in full virulence; defects of cell walls can affect appressorium formation and result in defective pathogenicity (Dou et al 2011;Xu 2000;Xu et al 1998). Cell wall integrity tests were conducted by growing a 5 mm mycelium plug of Guy11 and mutant fungi on CM medium plates containing 200 g/mL of Congo red (Sangon Co., Shanghai, China) followed by incubation at 25 • C under continuous light.…”
Section: Stress Condition Growth Assaysmentioning
confidence: 99%
“…Cell wall composition in M. oryzae plays an important role in full virulence; defects of cell walls can affect appressorium formation and result in defective pathogenicity (Dou et al 2011;Xu 2000;Xu et al 1998). Cell wall integrity tests were conducted by growing a 5 mm mycelium plug of Guy11 and mutant fungi on CM medium plates containing 200 g/mL of Congo red (Sangon Co., Shanghai, China) followed by incubation at 25 • C under continuous light.…”
Section: Stress Condition Growth Assaysmentioning
confidence: 99%
“…81 MoSec22 and MoVam7, the orthologs of yeast SNARE proteins Sec22 and Vam7, can also be demonstrated to have functions in vacuole assembly, which underlie the growth, conidiation, appressorium formation, and pathogenicity of M. oryzae. 82,83 Similarly, MoMon1 and MoYpt7 are the orthologs of the yeast proteins Mon1 and Ypt7.…”
Section: Molecular Mechanisms Of Autophagy In Pathogenic Fungimentioning
confidence: 99%
“…Extracellular peroxidase and laccase are required for the pathogenicity of certain fungi7344041. CR and 2’-azino-di-3- ethylbenzathiazoline-6-sulfonate (ABTs) are used as indicators for the presence of extracellular laccase and peroxidase, respectively42.…”
Section: Resultsmentioning
confidence: 99%
“…Recently studies showed that endocytosis is conserved from yeast to filamentous fungi, and mammalian cells, which emphasizes the importance of endocytosis for eukaryotic cells5. In yeast and plant pathogenic fungi, endocytosis is extensively involved in cell polarity establishment, hyphal growth, and/or virulence67891011.…”
mentioning
confidence: 99%
See 1 more Smart Citation